(untitled) - Vargus, L. T.; McBain, Tim ([Place of publication not identified], 2017)
A sniper along I-20 kills eight and causes a 36 car pileup. Brutal. Efficient. The next morning, the same individual stalks through a grocery store parking lot with a handgun. He takes out six innocent shoppers along with the stores front window before fleeing without a trace. By the time Special Agent Violet Darger arrives in Atlanta, the city teeters toward panic. No one dares to venture out. A killer walks among them. A shadow. And the public cowers just the way he wants them to. Once more Agent Darger must identify with a murderer, must stare into the darkness to anticipate his next move. Putting herself in his head may be the only way to stop him. The longer she takes, the higher the death toll.
Keywords: United States; Federal Bureau of Investigation; Officials and employees; Fiction; Investigation; Fiction; Fiction; Serial murders; Murder; Atlanta (Ga.); Fiction; Georgia; Fiction; Detective and mystery fiction; Thrillers (Fiction)